OPTIMIZING PRODUCTIVE ZAKAT THROUGH EMPOWERING MSMES TO MANAGE THE ECONOMIC IMPACT OF COVID-19 (ANALYSIS OF THE POTENTIAL OF ZAKAT IN EMPOWERING MSMES TO ADDRESS MACROECONOMIC PROBLEMS DUE TO COVID-19) - Vira Prajna Cantika; Muhammad Zulhamdi; Sulistiani Indriyastuti (ICO EDUSHA, 2020)
COVID-19 global pandemic has an impact on various aspects including the economic sector. At the end of July 2020, it was recorded that around 3.5 million workers were affected by the COVID-19 pandemic and the MSME sector was the most affected sector so it was necessary to implement policies to reduce the potential for higher losses. Zakat is a maaliah ijtima'iyyah worship that has strategic potential and contributes to the development of the people's welfare. The aim of this study is to review the potency of Zakat as the empowerment of MSMEs. The method used is a literature study performed by conducting several keywords such as policy, productive zakat, MSMEs, economic impact, COVID- 19. The search results were extracted based on inclusion and exclusion criteria. The final inclusion was synthesized in a descriptive or qualitative approach. Based on the literature obtained, zakat has a potential of 340 trillion, and when it is be produced it will be more effective in alleviating economic problems because the benefits can continue to grow for a long time. Meanwhile, MSMEs have a share of around 99.99% of the total business actors in Indonesia, and their empowerment is more effective because they are allocated directly to the needs of small businesses. Therefore, optimizing productive zakat by empowering MSMEs has good potential to overcome the economic impact of Covid-19. Keywords : Zakat, UMKM, Covid-19, Economic Impact, Policy